Cultural maintenance within the Tamil minority in Kuching: spanning three generations - Ponmalar, N.A.; Dealwis, C.; David, M.K. (Taylor & Francis, 2016)
This paper intends to determine whether the minority Tamil immigrant community in Kuching, Sarawak still maintains its heritage culture or has assimilated it with the dominant cultures in Sarawak. Are the Tamils in Kuching still maintaining their cultural norms? The data comes from a set of questionnaires investigating language, social and cultural identity, and unstructured interviews spanning three generations. The results show that, while some assimilation has occurred, the community has maintained its cultural identity. The most interesting revelation is the growing number of the younger generation who are adapting their heritage and cultural norms, clearly demonstrating Gibson’s accommodation and acculturation without assimilation.